Observation of the suppressed ADS modes B± → [π±K∓π+π−]DK± and B± → [π±K∓π+π−]Dπ± - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physics letters, 2013)
An analysis of B±→DK± and B±→Dπ± decays is presented where the D meson is reconstructed in the four-body final state K±π∓π+π−. Using LHCb data corresponding to an integrated luminosity of 1.0fb−1, first observations are made of the suppressed ADS modes B±→[π±K∓π+π−]DK± and B±→[π±K∓π+π−]Dπ± with a significance of 5.1σ and greater than 10σ, respectively. Measurements of CP asymmetries and CP-conserving ratios of partial widths from this family of decays are also performed. The magnitude of the ratio between the suppressed and favoured B±→DK± amplitudes is determined to be rBK=0.097±0.011.
Im Titel sind "±", "∓", "+" und "-" hochgestellt und "D" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 585
Gesehen am 27.04.2021